Influence of backside loading on the floating mass transducer: An in vitro experimental study. (28th November 2017) - Gostian, A.‐O.; Otte, M.S.; Pazen, D.; Ortmann, M.; Schwarz, D.; Hüttenbrink, K.B.; Beutner, D.
Abstract : Hypothesis: The vibration of the floating mass transducer (FMT) of a single active middle‐ear implant (AMEI) is distinctly influenced by the properties of the material coupled to its back side. Background: In round window vibroplasty, the FMT needs to be padded against the surrounding bone opposite from the round window membrane. This represents one factor influencing its performance as a round window driver. Therefore, we examined the effects of different materials linked to the back side of an FMT on its vibration range. Methods: The back side of an FMT was glued to a silicone cylinder 1.0 mm in diameter and 1.0 mm – 1.5 mm in length and of 40A, 50A or 70A Shore hardness; to cartilage of equivalent size; or to a round window soft coupler (RWSC), all firmly fixed on a steel plate. The vibrations were determined by a laser Doppler vibrometer (LDV) measuring the velocity of the centre point on the front side of the FMT. Results: The materials on the back side of the FMT significantly influenced the vibration range of the FMT. The RWSC and silicone of 40A Shore hardness allowed for the highest detected velocities, while cartilage led to a distinct reduction similarly to 70A silicone. Conclusion: The coupling on the back side of an FMT distinctly affects its vibration range. In this regard, the RWSC and silicone of 40A Shore hardness yield the least impairment of vibration. Thus, the RWSC may be a feasible option in round window vibroplasty when additionally connected to the FMT opposite from the round window membrane.